Nanozyme-driven self-assembled rhein gels for osteoarthritis therapy: Alleviating chondrocyte inflammation by reprogramming macrophages - Jian Jiang; Chao Song; Xuefeng Hou; Kangjie Xu; Zhongkai Ji; Lei Fan; Juqun Xi; Ailang Zhang (Materials Today Bio)
Osteoarthritis (OA), the fourth leading cause of global disability, is marked by progressive cartilage loss, synovial inflammation, and dysregulated bone remodeling. Current therapeutic strategies are hindered by systemic adverse effects and insufficient intra-articular drug bioavailability, underscoring the demand for enhanced delivery mechanisms. In this study, we developed a CeO2 nanozyme-driven gel system synergistically integrated with the herbal monomer rhein (RH). The coordinatively unsaturated sites on the CeO2 nanozymes triggered RH self-assembly into a gel through surface coordination interactions. Comprehensive characterization demonstrated that the CeO2/RH gels exhibit synergistic reactive oxygen/nitrogen species (RONS)-scavenging capability, leveraging both the antioxidant enzyme-mimetic activity of CeO2 and the intrinsic properties of RH. The redox-modulatory activity of CeO2/RH gels promoted macrophage polarization from M1 pro-inflammatory to M2 anti-inflammatory phenotypes through phenotypic reprogramming. This immunomodulatory shift substantially reduced inflammatory mediator secretion in macrophages, thereby suppressing chondrocyte apoptosis and senescence through downregulation of the IL-6/JAK2/STAT1 signaling axis via macrophage-chondrocyte crosstalk. In vivo validation using a modified Hulth-induced rat OA model demonstrated the CeO2/RH gels’ therapeutic superiority. Collectively, our findings establish the CeO2/RH gels as a synergistic therapeutic platform for OA intervention, demonstrating dual competency in RONS-scavenging precision and immunomodulatory microenvironment remodeling through redox-biology-mediated cellular cross-talk regulation.